ANALISIS PENDEKATAN SANITASI DALAM MENANGANI STUNTING (STUDI LITERATUR) - syamsuddin syam; Ulfa Zafirah Anisah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2020)
Sanitation is the prevention of disease by eliminating or controlling environmental factors that form a link in disease transmission. Poor sanitation can cause infectious diseases in toddlers and can lead to stunting. Stunting or short is a condition of failure to thrive in infants (0-11 months) and children under five (12-59 months) as a result of chronic malnutrition, especially in the first 1,000 days of life so that the child is too short for his age.            This study aims to determine the sanitation factor with the incidence of stunting. This type of research is a literature study, namely by collecting data in the form of secondary data obtained from the literature and the results of previous studies that examine the relationship between independent and dependent variables. The sample in this literature study research is 5 journals related to the title.            The results of the study showed that there were 5 journals on sanitation approaches in dealing with the incidence of stunting which was influenced by access to latrines, washing hands with soap, clean water facilities, sewerage channels, and they were stated to have a significant relationship with the incidence of stunting.            Based on the results, it can be concluded that poor sanitation will increase the risk of stunting in toddlers. Things that can be suggested are the control of risk factors for stunting, namely improving and maintaining latrine access, washing hands with soap, clean water facilities and sewerage channels. Keywords: Latrine Access, Handwashing With Soap, Clean Water Facilities, Sewerage, Sanitation, Stunting